ChatGPT’s Role in Enhancing Marketing Communication Strategy: Insights from Consultancy and Corporate Industries - Jeovannie, Abigail; Feima Sarah Firdhausyah; Fardhania Putri Utami (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study explores the role of ChatGPT in enhancing marketing communication strategies across consultancy and corporate industries, focusing on the increasing prominence of AI technologies like Generative AI. The phenomenon of AI-driven communication is critical due to its potential to transform marketing practices, making this research timely and relevant. The study aims to assess the effectiveness of ChatGPT in improving user satisfaction, productivity, and the development of marketing strategies, offering practical insights into its implementation. It addresses gaps in existing literature by providing empirical data on ChatGPT’s application in diverse sectors, including FMCG, financial, educational consultancy, marine, and hospitality. Grounded in marketing communication and marketing management theories, the research connects these concepts with ChatGPT's capabilities in content creation and brand messaging consistency. The methodology employs a qualitative approach with in-depth interviews and a phenomenological design, aligning with the study's objectives to derive comprehensive insights from industry professionals. The findings suggest that while ChatGPT offers significant benefits, its effectiveness is context-dependent, highlighting the need for tailored strategies to optimize its application in marketing communication. This study provides a foundation for future exploration of AI's evolving role in digital marketing.